Use of a waste-based binder for high water content soil treatment - Lam, Kok Pang (2020)
In recent years, roads in Singapore have had to be constructed on reclaimed land using marine clay as fill materials. Improving the engineering properties of the high water content, soft clayey soil in the reclaimed land in a cost-effective way before road construction becomes a challenge. It is expensive to treat high water content soil using cement because the amount of cement required would be excessive. In this paper, a study on the potential use of a waste-based binder as a substitute for portland cement for the improvement of high water content soil is presented. A series of laboratory tests were carried out to assess the undrained shear strength of binder-treated marine clay compared with the use of cement. The test results indicated that for soil with a high initial water content, the use of waste-based binder could shorten the curing period by about 20% while achieving the same unconfined compressive strength or increase the undrained shear strength at 14 or 28 days by 20 to 50% compared with the marine clay treated with cement of the same dosage. The aging effect of the waste-based binder was stronger. A microstructural study also shows that there are interlocking matrixes produced between soil particles in the binder-treated soil that contributes toward the increase in shear strength in the soil.